A LÍNGUA VERNÁCULA EM TRAINSPOTTING: UM ESTUDO COMPARATIVO MULTIMIDIÁTICO SOBRE O USO DO SCOTS EM DIFERENTES ADAPTAÇÕES DA OBRA DE IRVINE WELSH - Ronaldo de Carvalho Gomes (2022)
This research analyses the use of the principal vernacular language of Scotland, named Scots, in the cinematographic adaptation, in the audiobook version and the original literary work version of Trainspotting (2004), by Irvine Welsh. Through a comparative multimediatic study, we investigated how the adaptation processes happened, in linguistic terms, and the role of the Scots language in each of the adaptations. We also investigated how these adaptations contribute to the comprehension of vernacular languages in literary works of the English language literature. To do so, we made a panoramic study of the historical events in Scotland that kept it separated from England for centuries and how, sometime later, they were united in the formation of the United Kingdom. Many historical events influenced the development of the linguistic variation in Welsh’s works. From this perspective, it was possible to glimpse the Scots language, its origins, and its role in the adaptation and the literary work analysed. We conclude that the results of this research may contribute to the spread of works outside the canon of the English language literature and the uses of different multimediatic resources when linguistic variations and vernacular languages are used. Key words: Trainspotting; Scots; Multimedia.